A radio music feature on contemporary christian music. - Tay, Cheryl Deborah Shu Ping. (2009)
This paper details the pre-production work done that facilitated the production process of this radio programme. This programme is a music feature on the Contemporary Christian Music scene in the United States of America and here in Singapore. There being very little documentation of Christian music, most of my resources on Contemporary Christian Music in America comes from past issues of Christian and music magazines, and the internet. As for the local Contemporary Christian Music scene, with the exception of an article in 8 Days magazine in 1996, nothing has been written on the subject so far. Hence, most of my information is gathered first-hand -- through interviews, as well as compiling past music chart results. It is hoped that more will come to be aware of this music genre with this project, especially its existence locally.